Metode Perbaikan Struktur pada Gedung BCA Kcp Ahmad Rivai Palembang - Rajinda Bintang (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
An investigation into the building is carried out to determine the suitability and safety of the building and the strength of the structure. The investigations to be carried out include field and laboratory investigations. This is done to determine the feasibility and safety of existing structures. Apart from that, it is also hoped that this investigation can provide recommendations regarding repair or strengthening methods if necessary, referring to the requirements for Structural Concrete for Buildings SNI 2847:2019 and Procedures for Earthquake Resistance Planning for Building and Non-Building Structures SNI 2847:2019. From the results of structural testing using UPV and Hammer Test, it was found that the structural system is an open frame consisting of plates, beams and columns using concrete material, while the joists use steel plinths. The reinforcing steel used uses plain iron U40 as flexible reinforcement with shear reinforcement with U24. The quality of concrete obtained respectively for column f'c 25 MPa, beam f'c 22 MPa and floor slab f'c 22 MPa. Based on the results of the floor leveling survey to record the potential for building subsidence or floor sagging using a water level, it was concluded that there was no slope found in the building as a whole. The deflection that occurs is local and relatively flat. To meet the requirements, strengthening was carried out by increasing the dimensions of the columns and beams, adding plates to the steel profiles on the flange and web.